3D/2D Bi2S3/SnS2 heterostructures: superior charge separation and enhanced solar light-driven photocatalytic performance. Issue 11 (2nd March 2021) - Paul, Sumana; Barman, Dulal; Chowdhury, Chandra; Giri, P. K.; De, Subodh Kumar
Abstract : A type-II band alignment between Bi2 S3 and SnS2 was established by theoretical investigation which accelerates photoinduced charge separation and improved the photocatalytic activity of the Bi2 S3 /SnS2 heterostructure. Abstract : In promoting the application of green and sustainable solutions towards the photodegradation of organic dyes and toxic ions, it is urgent to fabricate semiconductor-based effective and stable photocatalysts. Constructing a heterojunction is the new way to accelerate the photoinduced charge separation to achieve enhanced photocatalytic activity. In this article, a novel 3D/2D heterostructure has been fabricated by a simple two-step solvothermal process. First of all, 3D Bi2 S3 urchins were synthesized and after that 2D SnS2 nanosheets were decorated on Bi2 S3 urchins. The formation of Bi2 S3 urchins was monitored at different reaction times and probed by scanning electron microscopy. Both theoretical calculations and experiments suggest that an epitaxial relationship was formed between the (211) plane of Bi2 S3 and the (012) plane of SnS2 . A type-II band alignment between Bi2 S3 and SnS2 was established by theoretical investigation, which accelerated photoinduced charge separation and improved the photocatalytic activity of the Bi2 S3 /SnS2 heterostructure. The surface area analysis of the Bi2 S3 /SnS2 heterostructure with different SnS2 loading was monitored and the increased surface area and the porous structure make the heterostructures more active than that of the pure one. Therefore, this 3D/2D heterostructure is found to be important as a new generation photocatalytic system.